Low-cost narrow-band zinc-aluminum-magnesium S550GD + ZM high-strength steel for photovoltaic support and preparation method thereof

By improving the purity of steel water during the preparation of the photovoltaic bracket, controlling the deterioration of the steel water, controlling the deterioration of the deformation, and the improvement of the thermal treatment process, the problem of bending, cracking and decapyice is prone to occur during processing and forming of photovoltaic brackets. High -intensity finished products and reduce production costs.

CN119372556APending Publication Date: 2025-01-28山西建龙实业有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411470032.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

During the processing and forming process, steel for photovoltaic brackets is prone to bending and cracking and dezincification problems, resulting in increased quality risks.

Method used

By increasing the purity of steel water, controlling the deformation rate, reducing the thickness of the oxidative iron skin of hot -rolled steel, improving the pickling effect, improving the hydrogen reduction efficiency, and setting a reasonable air -fuel ratio, low -cost narrow belt zinc, aluminum magnesium S550GD+ZM high -strength steel.

Benefits of technology

Effectively reduces the risk of cracking and decapyices, improves the strength and quality of the finished product, meets the requirements of photovoltaic brackets, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372556A_ABST
    Figure CN119372556A_ABST
Patent Text Reader

Abstract

The invention discloses low-cost narrow-band zinc-aluminum-magnesium S550GD + ZM high-strength steel for a photovoltaic support and a preparation method of the low-cost narrow-band zinc-aluminum-magnesium S550GD + ZM high-strength steel, belongs to the technical field of preparation of narrow-band steel for the photovoltaic support, and solves the technical problems that steel for the photovoltaic support is easy to crack during bending and high in dezincification risk in the processing and forming process. According to the solution, the low-cost narrow-band zinc-aluminum-magnesium S550GD + ZM high-strength steel for the photovoltaic support comprises the following components in percentage by mass: less than or equal to 0.06 wt% of C, less than or equal to 0.05 wt% of Si, 0.15 wt%-0.25 wt% of Mn, less than or equal to 0.025 wt% of P, less than or equal to 0.020 wt% of S, 0.020 wt%-0.035 wt% of Als and the balance of Fe and inevitable impurities. The alloy is prepared through smelting, hot rolling, acid pickling, cold rolling, degreasing and heat treatment in sequence. The production cost is reduced, after the C-shaped steel is processed by a customer, the dezincification and cracking conditions are avoided, and the use requirements are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of narrow strip steel preparation for photovoltaic brackets, and specifically relates to a low-cost narrow strip zinc-aluminum-magnesium S550GD+ZM high-strength steel for photovoltaic brackets and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of the photovoltaic industry, the demand for photovoltaic steel has increased, among which photovoltaic brackets can account for more than 70% of the photovoltaic steel. The photovoltaic bracket steel mainly includes three products: hot-dip galvanized, hot-dip galvanized aluminum-magnesium, and weathering steel. Zinc-aluminum-magnesium products have occupied a dominant position in the market due to their low production cost, good corrosion resistance, and good appearance quality. With the full promotion of zinc-aluminum-magnesium photovoltaic brackets, high strength and lightweight have become the development trend of the industry. High-strength steel S450GD+ZM and S550GD+ZM have begun to gradually replace traditional S250GD+ZM and S350GD+ZM, which not only improves the safety performance of photovoltaic brackets, but also saves steel, thereby reducing construction costs.

[0003] By testing the microstructure of the finished steel for photovoltaic brackets, it was found that the lattice had dislocation marks, distortions, and other forms, which resulted in the incomplete release of internal stress in the organization. Therefore, cracking problems are prone to occur when the finished product is bent and formed. At the same time, the production of this product requires a low-temperature annealing process. After the plate temperature is reduced, the plate temperature of the strip in the reduction section is reduced, which reduces the reduction efficiency of hydrogen, and easily leads to the iron oxide on the surface of the strip not being completely reduced. The Fe2Al5 alloy layer cannot be formed on the surface of the substrate in the zinc liquid, resulting in poor adhesion of the zinc layer and dezincification problems. In short, although high-strength steel S450GD+ZM and S550GD+ZM can greatly reduce production costs, the quality risk of the finished product is relatively increased, and bending cracking and dezincification problems are prone to occur.

[0004] Experts and scholars solve the problems existing in the existing technology through the following aspects: (1) Ingredient design

[0005] (2) Controlling the cold rolling deformation rate Cold rolling mill is used for rolling production, and the cold rolling deformation rate is controlled. During cold rolling, work hardening (work hardening is sometimes also called deformation strengthening) effect is produced, the grains inside the rolled piece are elongated, flattened, and broken, the lattice is twisted and distorted, the grains are sheared and slipped, and the dislocation density is continuously increased, resulting in enhanced interaction during dislocation movement, increased resistance to dislocation movement, and increased deformation resistance, thereby improving the strength of the parent material; (3) Controlling the annealing non-recrystallization rate Further control the annealing non-recrystallization rate to prevent the strip from undergoing complete recrystallization annealing, inhibit grain nucleation and growth, and thus inherit most of the deformation structure characteristics before annealing. The microstructure morphology and metallographic photos of the S550GD+ZM strip prepared by the traditional process of recovery recrystallization are shown in Figure 2. Figure 1 , Figure 2 As shown, the strength of the finished product is improved so that the yield strength and tensile strength of the material meet the requirements of high-strength steel.

[0006] Existing technologies can significantly improve material strength through deformation strengthening, but the plasticity is greatly reduced. Compared with traditional strengthening methods, although it can significantly reduce alloy costs, the risk of cracking and dezincification of steel is very high. Therefore, higher requirements are placed on the purity of molten steel, deformation rate, and annealing process. Summary of the invention

[0007] The main purpose of the present invention is to overcome the deficiencies in the prior art and solve the technical problems of easy cracking and high risk of dezincification during bending during the processing and forming of steel for photovoltaic brackets. The present invention provides a low-cost narrow-band zinc-aluminum-magnesium S550GD+ZM high-strength steel for photovoltaic brackets and a preparation method thereof.

[0008] The idea of ​​the present invention to solve the cracking problem is: (1) Improve the purity of molten steel and reduce harmful elements and inclusions. Changing the deoxidation method to aluminum deoxidation in the smelting stage can increase the deoxidation depth and reduce the generation of inclusions. In terms of composition design, reduce the content of harmful elements such as C, P, and S, improve the quality of molten steel, and reduce the risk of cracking; (2) Set a reasonable deformation rate to ensure that the strength of the strip is improved while preventing excessive internal stress from exacerbating the risk of cracking. When the deformation rate is too low, the internal lattice distortion is small, which will result in the strip strength failing to meet the requirements after work hardening; when the deformation rate is too high, the internal lattice deformation is large, the internal stress increases significantly, and the risk of cracking increases; (3) Limited application scenarios: The C-type bracket and square tube in the photovoltaic bracket are simple to form and have low requirements on material plasticity, so they can be used as a direction for promotion and application.

[0009] The idea of ​​the present invention to solve the cracking problem is: (1) Reduce the thickness of the oxide scale of hot-rolled strip. Since the hot-rolled strip production line has no means of controlled rolling and controlled cooling, the process is optimized in terms of heating time, starting rolling temperature, final rolling temperature, ultra-fast cooling, coiling temperature, etc. to minimize the thickness of the oxide scale and form an oxide scale component that is easy to pickle and peel off; (2) Increase the pickling temperature and concentration to improve the pickling effect of the strip and prevent under-pickling of the substrate surface; (3) Increase the concentration and temperature of the alkali solution in the cleaning section to clean the oil and residual iron on the surface of the strip; (4) Set a reasonable air-fuel ratio. The annealing furnace uses open flame direct heating. Before heating, air and blast furnace gas are mixed in a certain ratio and sent to the burner for combustion. When there is excess air, it is very easy to oxidize the strip and generate iron oxide; when there is too little air, the combustion efficiency is reduced and the gas cost is increased; (5) Improve hydrogen reduction efficiency. The protective gas in the annealing furnace is a mixture of H2 and N2, with hydrogen generally accounting for 30-35%. Since the present invention adopts a low-temperature annealing process, which reduces the reduction reaction rate of the strip in the reduction section, it is necessary to increase a certain amount of hydrogen to improve its reduction efficiency and prevent the iron oxide on the surface of the strip from being completely reduced.

[0010] The present invention is achieved through the following technical solutions: A low-cost narrow-band zinc-aluminum-magnesium S550GD+ZM high-strength steel for a photovoltaic support, wherein the composition and mass percentage thereof are: C: ≤0.06wt%, Si≤0.05wt%, Mn: 0.15wt%~0.25wt%, P≤0.025wt%, S≤0.020wt%, Als: 0.020wt%~0.035wt%, and the rest are Fe and unavoidable impurities.

[0011] A method for preparing low-cost narrow-band zinc-aluminum-magnesium S550GD+ZM high-strength steel for photovoltaic brackets, comprising the following steps: S1. Melting: Weigh the raw materials according to the composition and mass percentage of low-cost narrow-band zinc-aluminum-magnesium S550GD+ZM high-strength steel for photovoltaic brackets, and successively carry out blast furnace smelting, converter, argon station slag washing, and continuous casting to obtain S550GD+ZM high-strength steel continuous casting billet; S2, hot rolling: 1) Heating system: When the S550GD+ZM high-strength steel continuous casting billet prepared in step S1 is cooled to an initial state of room temperature, the continuous casting billet is sent to a heating furnace for heating, the heating temperature of the preheating section is 650°C-950°C, the heating temperature of the first heating section is 900°C-1220°C, the heating temperature of the second heating section is 1150°C-1270°C, the heating temperature of the soaking section is 1180°C-1250°C, each section is heated continuously, and the total heating time is ≥100min; When the S550GD+ZM high-strength steel continuous casting billet prepared in step S1 is cooled to not less than 300°C, the continuous casting billet is sent to a heating furnace for heating, the heating temperature of the preheating section is 800°C~1050°C, the heating temperature of the first heating section is 1050°C~1200°C, the heating temperature of the second heating section is 1120°C~1260°C, the heating temperature of the soaking section is 1180°C~1250°C, each section is heated continuously, and the total heating time is ≥80min; 2) Hot rolling process parameters are: When the S550GD+ZM high-strength steel continuous casting billet is discharged from the roller table of the heating furnace, the initial rolling temperature of the continuous casting billet is ≥1050℃, the final rolling temperature is 860±30℃, the ultra-fast cooling temperature is 790±20℃, and the coiling temperature is ≤680℃; S3, pickling: the S550GD+ZM high-strength steel strip prepared after hot rolling in step S2 is sequentially sent to the first pickling tank and the second pickling tank for pickling, the pickling temperature is 75°C~85°C; wherein, the concentration of HCl in the first pickling tank is ≥50g / L, and the concentration of Fe 2+ Concentration ≤140g / L, HCl concentration in the second pickling tank ≥160g / L, Fe 2+ Concentration ≤60g / L; S4, cold rolling: cold rolling the S550GD+ZM high-strength steel strip after pickling in step S3, the cold rolling process parameters are: pH value of the emulsion ≥ 6, concentration of emulsion oil ≥ 1.5%, emulsion temperature 45°C ~ 55°C, emulsion conductivity ≤ 500μs / cm, cold rolling deformation rate 40% ~ 60%; S5, degreasing: First, alkaline washing is performed in an alkaline degreasing solution, the free alkali point of the degreasing solution is 20Pt~30Pt, and the alkaline washing temperature is 70℃±5℃; then, the degreased steel strip is rinsed with clean water, and the rinsing temperature is 60℃±5℃; finally, the rinsed steel strip is dried, and the drying temperature is 80℃~110℃; S6. Heat treatment: the steel strip degreased in step S5 is fed into an annealing furnace, the protective atmosphere in the annealing furnace is a mixed atmosphere of hydrogen and nitrogen, the volume ratio of hydrogen to nitrogen in the protective atmosphere is 40%-50%, the TV value of the annealing furnace is set to 125-130, TV value = steel strip thickness value × feed speed value, air-fuel ratio is 0.52-0.57, open flame plate temperature is 600°C-620°C, radiation section plate temperature is 600°C-620°C, zinc pot temperature is 430°C-450°C, zinc liquid temperature is 455°C-460°C, and low-cost zinc-aluminum-magnesium S550GD+ZM high-strength narrow strip steel for photovoltaic brackets is obtained.

[0012] Furthermore, aluminum deoxidation is used in the step S1.

[0013] Furthermore, in step S2, the water temperature sprayed from the ultra-fast cooling outlet is ≤35°C, the water pressure is >0.9MPa, and the nozzle blockage rate is ≤5%.

[0014] Furthermore, in step S4, emulsion oil is added to the emulsion 1 hour before use.

[0015] Compared with the prior art, the present invention has the following beneficial effects: Compared with traditional S550GD+ZM strip steel, the Mn content of the present invention is reduced by about 0.6%, and it does not contain Nb and Ti elements. On the basis of component design, the aluminum deoxidation slag washing process is adopted in steelmaking to replace the refining process. At the same time, the annealing temperature is reduced to reduce the gas consumption cost. Taking all factors into consideration, the cost is reduced by about RMB 324 / ton. In addition, after the zinc-aluminum-magnesium S550GD+ZM high-strength narrow strip steel is processed into C-shaped steel by the customer, there is no dezincification and cracking, which meets the use requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Microstructure morphology of S550GD+ZM strip steel prepared by traditional process recovery recrystallization; Figure 2 for Figure 1 A partial enlarged photo of Figure 3 The microstructure morphology photo of the zinc-aluminum-magnesium S550GD+ZM high-strength narrow strip steel prepared by the present invention; Figure 4 for Figure 3 A partial enlarged photo of the . DETAILED DESCRIPTION

[0017] The present invention is further described in detail below in conjunction with the accompanying drawings. Example 1

[0018] A method for preparing low-cost narrow-band zinc-aluminum-magnesium S550GD+ZM high-strength steel for photovoltaic brackets, comprising the following steps: S1. Smelting: According to the composition and mass percentage of low-cost narrow-band zinc-aluminum-magnesium S550GD+ZM high-strength steel for photovoltaic brackets, raw materials are weighed, and blast furnace smelting, converter, argon station slag washing, and continuous casting (using stopper rod package production) are sequentially carried out. The deoxidation method in the smelting stage adopts an aluminum deoxidation slag washing process instead of a refining process to obtain a S550GD+ZM high-strength steel continuous casting billet; In this embodiment 1, the composition and mass percentage of low-cost narrow-band zinc-aluminum-magnesium S550GD+ZM high-strength steel for photovoltaic brackets are: C: 0.06wt%, Si: 0.03wt%, Mn: 0.20wt%, P: 0.022wt%, S: 0.015wt%, Als: 0.035wt%, and the rest are Fe and unavoidable impurities; S2, hot rolling: 1) The heating system is as follows: the S550GD+ZM high-strength steel continuous casting billet prepared in step S1 is cooled to room temperature of 25°C, and then sent into a heating furnace for heating, the heating temperature of the preheating section is 828°C, the heating temperature of the first heating section is 1086°C, the heating temperature of the second heating section is 1200°C, the heating temperature of the soaking section is 1205°C, each section is heated continuously, and the total heating time is ≥100min; 2) Hot rolling process parameters are as follows: when the S550GD+ZM high-strength steel continuous casting billet is discharged from the heating furnace roller, the initial rolling temperature of the continuous casting billet is 1065℃~1094℃, the final rolling temperature is 855℃~882℃, the ultra-fast cooling temperature is 770℃~803℃, and the coiling temperature is 515℃~642℃; the water temperature of the ultra-fast cooling outlet spray is 28℃, the water pressure is 0.95MPa, and the nozzle blockage rate is 1.2%; S3, pickling: the S550GD+ZM high-strength steel strip prepared after hot rolling in step S2 is sequentially sent to the first pickling tank and the second pickling tank for pickling at a temperature of 82°C; wherein the concentration of HCl in the first pickling tank is 62.94 g / L, and the concentration of Fe 2+ The concentration is 118.81 g / L, the concentration of HCl in the second pickling tank is 189.48 g / L, and the concentration of Fe 2+ The concentration is 18.91 g / L; S4, cold rolling: cold rolling the S550GD+ZM high-strength steel strip after pickling in step S3, the cold rolling process parameters are: the pH value of the emulsion is 6.50, the concentration of the emulsion oil is 2.2%, the emulsion temperature is 45°C, the emulsion conductivity is 389μs / cm, and the cold rolling deformation rate is 52%; the emulsion oil is added to the emulsion 1 hour before use; S5, degreasing: First, alkaline washing is performed in an alkaline degreasing solution, the free alkaline point of the degreasing solution is 25Pt, and the alkaline washing temperature is 67°C; then, the degreased steel strip is rinsed with clean water at a rinsing temperature of 57°C; finally, the rinsed steel strip is dried at a drying temperature of 92°C; S6. Heat treatment: the steel strip degreased in step S5 is fed into an annealing furnace. The protective atmosphere in the annealing furnace is a mixed atmosphere of hydrogen and nitrogen. The volume ratio of hydrogen to nitrogen in the protective atmosphere is 40%-50%. The TV value of the annealing furnace is set to 130, TV value = the value of the steel strip thickness × the value of the feeding speed, the air-fuel ratio is 0.52, the open flame plate temperature is 613°C, the radiation section plate temperature is 612°C, the zinc pot temperature is 435°C, the zinc liquid temperature is 455°C, and the zinc liquid selects conventional chemical composition and its ratio (Zn content is about 93.5%, and the other main components also include 3.5% Al and 3% Mg), to obtain low-cost zinc-aluminum-magnesium S550GD+ZM high-strength narrow strip steel for photovoltaic brackets.

[0019] The microstructure of the zinc-aluminum-magnesium S550GD+ZM high-strength narrow strip steel prepared in this embodiment is as follows: Figure 3 and Figure 4As shown, no obvious inclusions were found, the grain size was II-III 8.5, the large grains were 7.5, the small grains were 9.5, the metallographic structure was F+P+free cementite K, the free cementite K rating was 1.5A, and about 60%-70% of the grains had not completed recrystallization. Through organizational comparison, it was found that the S550GD+ZM organization produced by deformation strengthening was elongated and irregular, showing that the grains were not fully recovered, and some grains had not yet nucleated and grown. The mechanical properties test results of zinc-aluminum-magnesium S550GD+ZM high-strength narrow strip steel are shown in Table 2 below. Example 2

[0020] A method for preparing low-cost narrow-band zinc-aluminum-magnesium S550GD+ZM high-strength steel for photovoltaic brackets, comprising the following steps: S1. Smelting: According to the composition and mass percentage of low-cost narrow-band zinc-aluminum-magnesium S550GD+ZM high-strength steel for photovoltaic brackets, raw materials are weighed, and smelting in a blast furnace, a converter, argon station slag washing, and continuous casting (using stopper rod packaging) are carried out in sequence. The deoxidation method in the smelting stage adopts an aluminum deoxidation slag washing process instead of a refining process to obtain a S550GD+ZM high-strength steel continuous casting billet; In this embodiment 2, the composition and mass percentage of low-cost narrow-band zinc-aluminum-magnesium S550GD+ZM high-strength steel for photovoltaic brackets are: C: 0.06wt%, Si: 0.04wt%, Mn: 0.21wt%, P: 0.019wt%, S: 0.014wt%, Als: 0.030wt%, and the rest are Fe and unavoidable impurities; S2, hot rolling: 1) The heating system is as follows: when the S550GD+ZM high-strength steel continuous casting billet prepared in step S1 is cooled to 355°C, it is then sent into a heating furnace for heating, the heating temperature of the preheating section is 860°C, the heating temperature of the first heating section is 1109°C, the heating temperature of the second heating section is 1197°C, the heating temperature of the soaking section is 1191°C, each section is heated continuously, and the total heating time is ≥80min; 2) Hot rolling process parameters are as follows: when the S550GD+ZM high-strength steel continuous casting billet is discharged from the heating furnace roller, the initial rolling temperature of the continuous casting billet is 1070℃~1102℃, the final rolling temperature is 860℃~888℃, the ultra-fast cooling temperature is 788℃~804℃, and the coiling temperature is 523℃~671℃; the water temperature of the ultra-fast cooling outlet spray is 30℃, the water pressure is 0.95MPa, and the nozzle blockage rate is 1%; S3, pickling: the S550GD+ZM high-strength steel strip prepared after hot rolling in step S2 is sequentially sent to the first pickling tank and the second pickling tank for pickling at a temperature of 84°C; wherein the concentration of HCl in the first pickling tank is 64.38 g / L, and the concentration of Fe 2+ The concentration is 138.64 g / L, the concentration of HCl in the second pickling tank is 172.46 g / L, and the concentration of Fe 2+The concentration is 20.40 g / L; S4, cold rolling: cold rolling the S550GD+ZM high-strength steel strip after pickling in step S3, the cold rolling process parameters are: the pH value of the emulsion is 6.37, the concentration of the emulsion oil is 2.3%, the emulsion temperature is 47°C, the emulsion conductivity is 401μs / cm, and the cold rolling deformation rate is 48%; the emulsion oil is added to the emulsion 1 hour before use; S5, degreasing: first, alkaline washing is performed in an alkaline degreasing solution, the free alkaline point of the degreasing solution is 28Pt, and the alkaline washing temperature is 72°C; then, the degreased steel strip is rinsed with clean water at a rinsing temperature of 57°C; finally, the rinsed steel strip is dried at a drying temperature of 89°C; S6. Heat treatment: the steel strip degreased in step S5 is fed into an annealing furnace. The protective atmosphere in the annealing furnace is a mixed atmosphere of hydrogen and nitrogen. The volume ratio of hydrogen to nitrogen in the protective atmosphere is 40%-50%. The TV value of the annealing furnace is set to 127, TV value = the value of the steel strip thickness × the value of the feeding speed, the air-fuel ratio is 0.53, the open flame plate temperature is 618°C, the radiation section plate temperature is 608°C, the zinc pot temperature is 437°C, the zinc liquid temperature is 455°C, and the zinc liquid selects conventional chemical composition and its ratio (Zn content is about 93.5%, and the other main components also include 3.5% Al and 3% Mg), to obtain low-cost zinc-aluminum-magnesium S550GD+ZM high-strength narrow strip steel for photovoltaic brackets. Example 3

[0021] A method for preparing low-cost narrow-band zinc-aluminum-magnesium S550GD+ZM high-strength steel for photovoltaic brackets, comprising the following steps: S1. Smelting: According to the composition and mass percentage of low-cost narrow-band zinc-aluminum-magnesium S550GD+ZM high-strength steel for photovoltaic brackets, raw materials are weighed, and smelting in a blast furnace, a converter, argon station slag washing, and continuous casting (using stopper rod packaging) are carried out in sequence. The deoxidation method in the smelting stage adopts an aluminum deoxidation slag washing process instead of a refining process to obtain a S550GD+ZM high-strength steel continuous casting billet; In this embodiment 3, the composition and mass percentage of low-cost narrow-band zinc-aluminum-magnesium S550GD+ZM high-strength steel for photovoltaic brackets are: C: 0.05wt%, Si: 0.05wt%, Mn: 0.21wt%, P: 0.022wt%, S: 0.012wt%, Als: 0.029wt%, and the rest are Fe and unavoidable impurities; S2, hot rolling: 1) The heating system is as follows: when the S550GD+ZM high-strength steel continuous casting billet prepared in step S1 is cooled to 400°C, it is then sent into a heating furnace for heating, the heating temperature of the preheating section is 882°C, the heating temperature of the first heating section is 1093°C, the heating temperature of the second heating section is 1232°C, the heating temperature of the soaking section is 1200°C, each section is heated continuously, and the total heating time is ≥80min; 2) Hot rolling process parameters are as follows: when the S550GD+ZM high-strength steel continuous casting billet is discharged from the roller of the heating furnace, the initial rolling temperature of the continuous casting billet is 1058℃~1704℃, the final rolling temperature is 865℃~890℃, the ultra-fast cooling temperature is 790℃~810℃, and the coiling temperature is 530℃~677℃; the water temperature of the ultra-fast cooling outlet spray is 28℃, the water pressure is 0.95MPa, and the nozzle blockage rate is 1.2%; S3, pickling: the S550GD+ZM high-strength steel strip prepared after hot rolling in step S2 is sequentially sent to the first pickling tank and the second pickling tank for pickling at a temperature of 85°C; wherein the concentration of HCl in the first pickling tank is 66.79 g / L, and the concentration of Fe 2+ The concentration is 127.58 g / L, the concentration of HCl in the second pickling tank is 170.28 g / L, and the concentration of Fe 2+ The concentration is 22.58 g / L; S4, cold rolling: cold rolling the S550GD+ZM high-strength steel strip after pickling in step S3, the cold rolling process parameters are: the pH value of the emulsion is 6.20, the concentration of the emulsion oil is 2.3%, the emulsion temperature is 50°C, the emulsion conductivity is 398μs / cm, and the cold rolling deformation rate is 45%; the emulsion oil is added to the emulsion 1 hour before use; S5, degreasing: First, alkaline washing is performed in an alkaline degreasing solution, the free alkaline point of the degreasing solution is 29Pt, and the alkaline washing temperature is 70°C; then, the degreased steel strip is rinsed with clean water at a rinsing temperature of 58°C; finally, the rinsed steel strip is dried at a drying temperature of 95°C; S6. Heat treatment: the steel strip degreased in step S5 is fed into an annealing furnace. The protective atmosphere in the annealing furnace is a mixed atmosphere of hydrogen and nitrogen. The volume ratio of hydrogen to nitrogen in the protective atmosphere is 40%-50%. The TV value of the annealing furnace is set to 125, TV value = the value of the steel strip thickness × the value of the feeding speed, the air-fuel ratio is 0.55, the open flame plate temperature is 615°C, the radiation section plate temperature is 611°C, the zinc pot temperature is 446°C, the zinc liquid temperature is 456°C, and the zinc liquid selects conventional chemical composition and its ratio (Zn content is about 93.5%, and the other main components also include 3.5% Al and 3% Mg), to obtain low-cost zinc-aluminum-magnesium S550GD+ZM high-strength narrow strip steel for photovoltaic brackets.

[0022] ; After testing, the finished products all meet the national standards.

[0023] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A low-cost narrow-band zinc-aluminum-magnesium S550GD+ZM high-strength steel for photovoltaic brackets, characterized by: The composition and mass percentage of the zinc-aluminum-magnesium S550GD+ZM high-strength steel are: C: ≤0.06wt%, Si≤0.05wt%, Mn: 0.15wt%~0.25wt%, P≤0.025wt%, S≤0.020wt%, Als: 0.020wt%~0.035wt%, and the rest are Fe and unavoidable impurities.

2. The method for preparing a low-cost narrow-band zinc-aluminum-magnesium S550GD+ZM high-strength steel for photovoltaic brackets as claimed in claim 1, characterized in that: The following steps are involved: S1. Melting: Weigh the raw materials according to the composition and mass percentage of low-cost narrow-band zinc-aluminum-magnesium S550GD+ZM high-strength steel for photovoltaic brackets, and successively carry out blast furnace smelting, converter, argon station slag washing, and continuous casting to obtain S550GD+ZM high-strength steel continuous casting billet; S2, hot rolling: 1) Heating system: When the S550GD+ZM high-strength steel continuous casting billet prepared in step S1 is cooled to an initial state of room temperature, the continuous casting billet is sent to a heating furnace for heating, the heating temperature of the preheating section is 650°C-950°C, the heating temperature of the first heating section is 900°C-1220°C, the heating temperature of the second heating section is 1150°C-1270°C, the heating temperature of the soaking section is 1180°C-1250°C, each section is heated continuously, and the total heating time is ≥100min; When the S550GD+ZM high-strength steel continuous casting billet prepared in step S1 is cooled to not less than 300°C, the continuous casting billet is sent to a heating furnace for heating, the heating temperature of the preheating section is 800°C~1050°C, the heating temperature of the first heating section is 1050°C~1200°C, the heating temperature of the second heating section is 1120°C~1260°C, the heating temperature of the soaking section is 1180°C~1250°C, each section is heated continuously, and the total heating time is ≥80min; 2) Hot rolling process parameters are: When the S550GD+ZM high-strength steel continuous casting billet is discharged from the roller table of the heating furnace, the initial rolling temperature of the continuous casting billet is ≥1050℃, the final rolling temperature is 860±30℃, the ultra-fast cooling temperature is 790±20℃, and the coiling temperature is ≤680℃; S3, pickling: the S550GD+ZM high-strength steel strip prepared after hot rolling in step S2 is sequentially sent to the first pickling tank and the second pickling tank for pickling, the pickling temperature is 75°C~85°C; wherein, the concentration of HCl in the first pickling tank is ≥50g / L, and the concentration of Fe 2+ Concentration ≤140g / L, HCl concentration in the second pickling tank ≥160g / L, Fe 2+ Concentration ≤60g / L; S4, cold rolling: cold rolling the S550GD+ZM high-strength steel strip after pickling in step S3, the cold rolling process parameters are: pH value of the emulsion ≥ 6, concentration of emulsion oil ≥ 1.5%, emulsion temperature 45°C ~ 55°C, emulsion conductivity ≤ 500μs / cm, cold rolling deformation rate 40% ~ 60%; S5, degreasing: First, alkaline washing is performed in an alkaline degreasing solution, the free alkali point of the degreasing solution is 20Pt~30Pt, and the alkaline washing temperature is 70℃±5℃; then, the degreased steel strip is rinsed with clean water, and the rinsing temperature is 60℃±5℃; finally, the rinsed steel strip is dried, and the drying temperature is 80℃~110℃; S6. Heat treatment: the steel strip degreased in step S5 is fed into an annealing furnace, the protective atmosphere in the annealing furnace is a mixed atmosphere of hydrogen and nitrogen, the volume ratio of hydrogen to nitrogen in the protective atmosphere is 40%-50%, the TV value of the annealing furnace is set to 125-130, TV value = steel strip thickness value × feed speed value, air-fuel ratio is 0.52-0.57, open flame plate temperature is 600°C-620°C, radiation section plate temperature is 600°C-620°C, zinc pot temperature is 430°C-450°C, zinc liquid temperature is 455°C-460°C, and low-cost zinc-aluminum-magnesium S550GD+ZM high-strength narrow strip steel for photovoltaic brackets is obtained.

3. The method for preparing a low-cost narrow-band zinc-aluminum-magnesium S550GD+ZM high-strength steel for photovoltaic brackets according to claim 2, characterized in that: In the step S1, aluminum deoxidation is performed.

4. The method for preparing low-cost narrow-band zinc-aluminum-magnesium S550GD+ZM high-strength steel for photovoltaic brackets according to claim 2, characterized in that: In step S2, the water temperature sprayed from the ultra-fast cooling outlet is ≤35°C, the water pressure is >0.9MPa, and the nozzle blockage rate is ≤5%.

5. The method for preparing low-cost narrow-band zinc-aluminum-magnesium S550GD+ZM high-strength steel for photovoltaic brackets according to claim 2, characterized in that: In step S4, emulsion oil is added to the emulsion 1 hour before use.

Citation Information

Cited By

  • 550MPa-grade hot-dip galvanized aluminum magnesium coated steel plate and preparation method thereof

    CN120555694A